Analysis of the Biological Quality of Clean Water in the Taha Quran Education Park - Taufik Abdullah; Azwaruddin Azwaruddin; Sri Wahyuningsih (Jurnal Pijar MIPA, 2025)
Clean water is a source of basic needs for all forms of life. Water quality must be ensured before use, and water sources must be monitored regularly. The use of unclean water is one of the causes of skin diseases. Various age groups can be affected by skin diseases, especially the age group of children, who are still vulnerable. The purpose of this study was to determine the quality of clean water in the Taha Qur'an Education Park, which was reviewed biologically. This type of research is Descriptive Qualitative. The population in this study were all the water taps in the Taha Qur'an Education Park. The selection of all samples as a population was due to the fact that there were only two water taps at the Taha Quranic Education Park. Based on the results of biological quality tests, including Coliform tests and Escherichia Coli tests obtained in water, it is known that the results of the coliform test obtained in sample A were 10 MPN / 100ml and in sample B 168MPN / 100 ml, and the results of Escherichia Coli in sample A were 15,000 MPN / 100ml and in Sample B 5,000 MPN / 100ml. The water used by the students is still considered unfit for consumption due to the presence of coliform and Escherichia coli bacteria, which can cause disease in humans. Treatment is needed to reduce the bacterial content in the sanitation facilities at the Taha Quranic Education Park.